Design of X-Cut and Z-Cut Lithium Niobate Whispering-Gallery-Mode Disk-Resonators With High Quality Factors - Yu Pan; Guoping Lin; Souleymane Diallo; Xianmin Zhang; Yanne K. Chembo (IEEE Photonics Journal)
We demonstrate the fabrication process of millimeter-size lithium niobate (LiNbO $_3$ ) whispering-gallery-mode (WGM) disk-resonators. We fabricate both $x$ - and $z$ -cut disk-resonators, starting from commercially available LiNbO $_3$ disks with diameters of 12 mm and thicknesses of 1 mm. We characterize these two WGM resonators using a prism coupling configuration. We find that both resonators feature high loaded quality factors, in both cases higher than $10^7$ at 1550 nm. We also investigate the polarization and thermal effects in these disk-resonators. The design of high- $Q$ LiNbO $_3$ disk-resonators with different orientations using the same platform will allow for a wide variety of potential applications in nonlinear and quantum photonics.